Aplikasi Photosynthetic Bacteria terhadap Pertumbuhan dan Hasil Tanaman Stroberi Didataran Rendah: Photosynthetic Bacteria Application on the Growth and Results of Strawberry Crops in Lowlands - Hariani, Mekka; Khalisa, Khalisa; Halim, Abdul; Mahdiannoor, Mahdiannoor (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
The strawberry plant has been known since Roman times, the strawberry plant is a herbaceous fruit plant. Herbaceous plants have wet stems and have no wood. Photosynthetic bacteria (PSB) are amazing autotrophic bacteria that can photosynthesize, photosynthetic bacteria are bacteria that can convert organic matter into amino acids or bioactive substances with the help of sunlight. Lowland in general are very large areas with relatively shallow elevations, which are less than 200 meters above sea level. The lowland are also known as floodplains or alluvial plains. The objectives of this research are (i) how is the growth and yield of strawberry plant with the application of PSB (Photosynthetic bacteria) (ii) what is the best dose of PSB for the growth and yield of strawberry plant. This research was conducted in Kebun Sari Village, Central Amuntai District, Hulu Sungai Utara Regency, South Kalimantan Province. It was carried out for 4 months starting from June to September 2022. This research was carried out using a RAK (Randomized Block Design) with a single factor studied was the concentration. 5 levels of PSB consisting of p0 0 ml PSB/l water, p1 5 ml PSB/l water, p2 10 ml PSB/l water, p3 15 ml PSB/l water, p4 20 ml PSB/l water. The results showed that the growth of strawberry plants had no effect on the provision of PSB Keywords : Lowlands, Media, Photosynthetic bacteria, Polybag, Strawberry